Case Report: Metabolic alterations and cholesterol esterification in a low-grade diffuse astrocytoma patient who progressed to glioblastoma at recurrence - Ijare, Omkar B.; Baskin, David S.; Powell, Suzanne Z.; Pichumani, Kumar (Frontiers in Oncology, 2025)
BackgroundMetabolic alterations during transformation of low-grade gliomas (LGGs) into high-grade glioblastomas (GBMs) remain incompletely understood. Particularly, IDH wildtype (IDHwt) diffuse astrocytomas harboring TERT promoter (TERTp) mutations, classified as molecular GBM under the 2021 WHO classification, may exhibit distinct metabolic and epigenetic features compared to histological WHO Grade 4 GBMs. Here, we conducted a detailed metabolomic comparison of tumor specimens from a patient initially diagnosed with WHO Grade 2 IDHwt diffuse astrocytoma carrying TERTp mutation, who subsequently progressed to a histologically confirmed WHO Grade 4 GBM upon recurrence.Case presentationA 66-year-old female patient underwent surgical resection of a WHO Grade 2 diffuse astrocytoma in April 2018. Molecular testing revealed IDH1-wildtype status and TERTp mutation, classifying the tumor as a molecular GBM. Following ~3.5 years of clinical stability, magnetic resonance imaging detected tumor recurrence. The patient underwent a second craniotomy in February 2022, with histopathology confirming progression to WHO Grade 4 GBM. Using untargeted proton nuclear magnetic resonance (1H NMR) spectroscopy, we analyzed aqueous-methanol and chloroform phases from methanol-chloroform-water extraction of tumor tissue from both time points. Compared to the primary tumor, the aqueous-methanol phase of the recurrent WHO Grade 4 GBM specimen showed decreased levels of neuronal and glial markers including N-acetylaspartate, myo-inositol, and scyllo-inositol. Elevated metabolites included phosphocholine, phosphoethanolamine, glycine, taurine, hypotaurine, branched-chain amino acids (leucine, isoleucine, valine), and notably alanine, which increased approximately 6-fold. Alanine likely serves as an alternative carbon source supporting tumor proliferation and aggressiveness. The chloroform phase showed the presence of cholesterol in both tumors; however, cholesteryl ester (CE) was detected only in the recurrent tumor. The CE-to-cholesterol ratio of 0.44 in the recurrent tumor suggests significant cholesterol esterification during malignant progression.ConclusionOur findings identify alanine accumulation and increased cholesterol esterification as key metabolic features accompanying malignant transformation from molecular GBM to histological WHO grade-4 GBM. These metabolic changes may serve as biomarkers of tumor progression and recurrence. Importantly, alanine detection via magnetic resonance spectroscopy offers promising potential for non-invasive glioma diagnostics. Furthermore, targeting cholesterol esterification pathways using Acyl-CoA:cholesterol acyltransferase inhibitors could provide a novel therapeutic approach, especially for low-grade astrocytomas with high risk of malignant progression and recurrence.